A Review of Vulnerary Application of Selected Medicinal Plants in Traditional Health Care - Thiruvengadarajan, V.S.; Rajasekaran, A.; Manimegalai, A.; Lal Muthukumar, V.; Mathialagan, P.; Santhosh, V.S.; Thamayanthi, T. (Pharmacognosy Reviews)
Wound healing and inflammation are highly intricate biological processes that work to restore the body’s tissue structure and function after injury. In recent years, growing interest has focused on plant-based bioactive compounds as promising therapeutic options, largely because of their proven effectiveness, safety, and low risk of side effects. A wide range of phytochemicals-such as flavonoids, alkaloids, tannins, saponins, terpenoids, and phenolic compounds-have shown strong wound-healing and anti-inflammatory potential. These natural compounds exert their effects through various mechanisms, including antioxidant defense, regulation of cytokine activity, stimulation of collagen formation, promotion of new blood vessel growth, and suppression of inflammatory mediators like prostaglandins and nitric oxide. By combining traditional herbal knowledge with modern pharmacological research, scientists have been able to validate and better understand the therapeutic roles of many medicinal plants in treating wounds and inflammation. This review seeks to explore and critically assess how plant-derived constituents contribute to tissue repair and inflammation control, outlining their underlying mechanisms, therapeutic potential, and future directions for developing innovative plant-based pharmaceuticals.
Keywords: Angiogenesis stimulation; Cytokines modulation; Herbal drugs; Oxidative Stress control; Tissue repair promotion; Wound healing.